Cost–benefit analysis of water conservation systems installed in household buildings in Nairobi County. Issue 6 (18th August 2022) - Shikuku, James; Munala, Gerryshom; Njuguna, Mugwima; Muhoro, Teckla; Gremley, Andrew; Nyakundi, Victor; Ali, Muhammad
ABSTRACT: Cost–benefit analysis of installed water conservation systems (piped water storage, water recycling, and rainwater harvesting) is important in management of water resources in urban areas. This study analysed water conservation systems installed in households in Nairobi County using 200 households' questionnaires. Benefit–cost ratio analysis indicated that the piped water storage system and rainwater harvesting system were viable with benefits at 2.80 and 2.03, respectively, while the water recycling system was not viable at 0.80. This study recommends installation of piped water storage and rainwater harvesting systems for quality, quantity, and reliable water to be availed in households within viable economic costs.